Cropland expansion - Schmidt, Emily; Thomas, Timothy S. (International Food Policy Research Institute, 2020)
Chapter 2, “Cropland Expansion,” uses spatially disaggregated satellite data to examine changes in land use over time at the national level. This is the first time that such dynamic analysis has been examined at this level. The data indicate a slowing in rate of cropland expansion in much of northern Ethiopia. The authors use results of econometric analysis of land use changes over time to estimate maximum potential economic cropland across space and potential land expansion. The analysis suggests little scope for further crop expansion in the drier parts of the highland but ample opportunities for increased crop cultivation on underused land with sufficient rainfall in parts of western regions (especially Benishangul-Gumuz and Gambella) and in the Oromia region.